UPAYA MENINGKATKAN PENGUASAAN KOHESI DAN KOHERENSI DENGAN PENDEKATAN KONTEKSTUAL BERBASIS PRODUK PADA MATA KULIAH ANALISIS WACANA - Winarsih, Eni (Widyabastra, 2012)
The aims of this research are: (1) Describing and explaining the learning of folklore by using STAD method; (2) improving studentsâ ability in appreciation of folklore by using STAD method;Â  (3)Â  describingÂ  theÂ  difficultiesÂ  thatÂ  facedÂ  inÂ  improvingÂ  studentsÂ  appreciationÂ  of folklore by using STAD method of students VII F SMP Negeri 11 Madiun.This subject of the research is students of class VII F SMP Negeri 11 Madiun. The object of the research is the using of STAD method in âBahasa dan Sastra Indonesiaâ learning process asÂ  theÂ  effortÂ  toÂ  improveÂ  studentsâÂ  abilityÂ  appreciationÂ  ofÂ  folklore.Â  DataÂ  resourceÂ  are:Â  (1) informant;Â Â  (2)Â Â  placeÂ Â  andÂ Â  event;Â Â  (3)Â Â  documents.Â Â Â Â Â  DataÂ Â  collectingÂ Â  techniqueÂ Â  are:Â Â  (1) observation; (2) deep interview; (3) questionnaire; (4) test. Data validity used is triangulation techniqueÂ  consistÂ  of:Â  (1)Â  dataÂ  triangulation;Â  (2)Â  methodÂ  triangulation;Â  (3)Â  informantÂ  review. Data analysis is by using comparative descriptive technique and critics analysis technique.The result of the research shows that using Student Team Achievement Division (STAD) can improveÂ  theÂ  abilityÂ  inÂ  appreciationÂ  ofÂ  folkloreÂ  ofÂ  studentsÂ  classÂ  VIIÂ  FÂ  SMPÂ  NegeriÂ  11 Madiun.Â  ItÂ  canÂ  beÂ  seenÂ  fromÂ  theÂ  resultÂ  ofÂ  pretestÂ  andÂ  posttestÂ  thatÂ  conductedÂ  duringÂ  three cycles.Â Â Â  AtÂ  theÂ  testÂ  beforeÂ  actionÂ  theÂ  numberÂ  ofÂ  studentsÂ  gettingÂ  scoreÂ  moreÂ  thanÂ  KKMÂ  (70, 00)Â  areÂ  16Â  studentsÂ  (40,Â  00%)Â  withÂ  averageÂ  scoreÂ  isÂ  65,Â  55.Â  AtÂ  firstÂ  cycleÂ  theÂ  numberÂ  of students getting more than KKM improves be 21 students (52, 50%). The improvement equal 12,Â  50%.Â  WhileÂ  classÂ  averageÂ  scoreÂ  65,Â  57Â  hasÂ  notÂ  reachedÂ  KKM.Â  AtÂ  secondÂ  cycle,Â  the improvement is 27 students equal 67, 50% has reached KKM or improvement 15% from first cycle,Â  withÂ  theÂ  averageÂ  classÂ  scoreÂ  68,925.Â  ThisÂ  improvementÂ  hasÂ  notÂ  reachedÂ  KKMÂ  70,Â  00 and class minimum score has not reached 75%. So the process is continued in to third cycle. AfterÂ  testÂ  inÂ  thirdÂ  cycleÂ  theÂ  numberÂ  studentsÂ  canÂ  reachedÂ  KKMÂ  areÂ  35Â  studentsÂ  (87,Â  50%) withÂ  theÂ  classÂ  averageÂ  scoreÂ  isÂ  73,525.Â  AtÂ  thirdÂ  cycleÂ  classÂ  minimumÂ  scoreÂ  hasÂ  beenÂ  more than 75%Â  and minimum ability score is 70.00.Â  ItÂ  can be conclude that the learning byÂ  using STAD method can improve quality and result learning. It also can be improve students ability in appreciation of folklore. Key Words: appreciation folklore, Student Team Achievement Division (STAD)